Clinical outcomes of Taiwanese patients with resected squamous cell carcinoma of the upper and lower gum. (July 2021) - Tsai, Chi-Ying; Lee, Shu Ru; Lee, Li-Yu; Hsueh, Chuen; Lin, Chien-Yu; Fan, Kang-Hsing; Wang, Hung-Ming; Hsieh, Chia-Hsun; Ng, Shu-Hang; Yeh, Chih-Hua; Lin, Chih-Hung; Tsao, Chung-Kan; et al.
Highlights: Compared to lower gum SCC, upper gum SCC had less favorable 5-year DSS and OS rates. Upper gum SCC had higher frequencies of aged ≥ 65 years and margin status ≤ 4 mm. Wide resection margins are recommended to improve outcomes of upper gum SCC. Abstract: Objectives: This large-scale cohort study was designed to compare the clinical outcomes of Taiwanese patients with squamous cell carcinoma (SCC) of the upper versus lower gum. Methods: Between 2004 and 2017, we identified 4244 patients with first primary SCC of the gum (694 upper gum; 3550 lower gum) who were treated with surgery either with or without adjuvant therapy. Of them, 1990 patients (329 upper gum; 1661 lower gum) enrolled from 2011 to 2017 had a higher number of histopathological variables and entered subgroup analyses. Five-year disease-specific survival (DSS) and overall survival (OS) rates served as outcome measures. Results: The 5-year DSS and OS rates of patients with upper gum SCC were lower than those of cases with lower gum SCC (65%/74%, p  < 0.0001; and 55%/65%, respectively, p  < 0.0001). Compared with lower gum SCC, upper gum SCC had a higher prevalence of the following variables: female sex, age ≥ 65 years, pNx (without neck dissection), no-betel chewing (2011–2017), no-smoking (2011–2017), and margin status ≤ 4 mm (positive and close margins, 2011–2017). On multivariable analysis, gum subsite (upper versus lower), age (≥65 versus  < 65 years), pT (T3 − 4 versus T1 − 2), pN (N1 − 3 versus N0/Nx), depth (≥10 mm versus  < 10 mm, 2011–2017), ENE (present versus absent, 2011–2017), and margins (≤4 mm versus  > 4 mm 2011–2017, only DSS) were identified as independent adverse prognostic factors for 5-year DSS and OS. Conclusions: Compared to lower gum SCC, upper gum SCC had less favorable 5-year outcomes. Wide resection margins are recommended to improve prognosis of upper gum SCC.